An exploration of Bob Mintzer's arrangement of footprints by wayne shorter for saxophone quintet and rhythm section / Affifi Adzlan Ahmad - Ahmad, Affifi Adzlan (Faculty of Music, 2014)
As a student majoring in music performance, I always perform jazz standards during my years of studies, but most of the time, I forgot the basic skills as I advance in my semester. This study started after I played the piece Footprints rearrange by Bob Mintzer myself. Firstly I have encountered difficulties on recognizing the harmony of the piece. It shows that I don't master the basic skills in harmony. This arrangement of Footprints has many harmonization of chords, using basic and simple harmony theory. By using simple rhythmic approach, Bob Mintzer has also created a long and interesting arrangement of Footprints, including an intro, musical transition, counterpoint, and outro. He also arrange this piece for a saxophone quintet accompanied by rhythm section.